URGENSI PEMBERLAKUAN ASURANSI KREDIT DALAM KREDIT JUAL BELI KENDARAAN BERMOTOR SEBAGAI IMPLEMENTASI PERLINDUNGAN TERHADAP AHLI WARIS - Fadhillah, Yansi (LPPM STIH Awang Long, 2023)
Motor vehicle credit insurance is a form of protection for motorized vehicles and consumers in credit agreements, namely vehicle insurance and life insurance. However, in the implementation, the insurance used in motor vehicle loans mostly uses only vehicle insurance, although life insurance is also very important, where this life insurance protects customers and heirs from the burden of paying off the remaining vehicle loans if the customer dies. In this writing it is aimed to find out the urgency of applying credit insurance in the sale and purchase of motor vehicle loans and as a basic knowledge for people who will apply for the purchase of motorized vehicles with a credit system. This paper describes the important points of credit insurance, the definition of credit insurance, the purpose of credit insurance, types of credit insurance, and laws and regulations related to credit insurance. It also explains why life insurance for car loans is very important for customers.